STUDI PARAMETER INTERAKSI AERODINAMIKA DAN STRUKTUR SAYAP SOLID MENGGUNAKAN METODE TWO-WAY FLUID STRUCTURE INTERACTION - WALDO PARLINDUNGAN, DAVID
High Altitude Long Endurance (HALE) is an unmanned vehicle that used as a civilian or military aircraft with mission such as telecommunication and observation. HALE aircraft is designed to operate at high altitude and long flight time. To achieve this, the wing needs to have higher aerodynamic efficiency and lightweight structure where it is designed as high aspect ratio wing and the structure material is composite. High aspect ratio will cause flexible wing and easily deformed due to bending. The deformation will change aerodynamic force and vice versa, thus the interaction between fluid and structure occur is called Fluid-Structure Interaction (FSI). In this work, we focus on parameter study for the interaction between fluid and structure of the HALE wing structure as a system without any single trigger of continuous trigger (gust) by using strong two-way coupling. The fluid solution was solved using unsteady RANS equation and turbulence model shear stress transport (SST), then structure solution was solved using spring equation of motion. Next, the interaction between fluid and structure were coupled using strong two-way coupling method. FSI simulation showed that the interaction between fluid and structured would cause oscillation in wing motion until it stopped at new position. The fluid solution showed that the parameter variation of freestream velocity increased aerodynamic characteristics, but it wasn’t significantly changed when Young Modulus increased. The structure solution gives structure response results in frequency, stress, and maximum deflection due to parameter variation at Young Modulus and freestream velocity.